ВЫБОР ТЕМЫ, СЮЖЕТ И ТИПИЧНОСТЬ В СОВРЕМЕННОЙ АЗЕРБАЙДЖАНСКОЙ ЛИТЕРАТУРЕ. - Аббасова, О. С. (Eurasian Journal of Philology Science and Education, 2015)
Speaking about creative qualities of the modern Azerbaijan literature first of all it is necessary to underline problems of a choice of a theme, a plot and typicalness. Because it is impossible to stand aside from understanding of the given problem in the decision of creative problems. In other words, would be inexpedient to estimate the creative parties of any art value, having ignored his theme, a plot and typicalness